2021
DOI: 10.1093/ijnp/pyab091
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Abnormalities of Olfactory-Related Regions in Subjective Cognitive Decline, Mild Cognitive Impairment, and Alzheimer’s Disease

Abstract: Background Odor identification (OI) dysfunction is an early marker of Alzheimer’s disease (AD), but it remains unclear how olfactory-related regions change from stages of subjective cognitive decline (SCD) and mild cognitive impairment (MCI) to AD dementia. Methods Two hundred and sixty-nine subjects were recruited in the present study. The olfactory-related regions were defined as the regions of interest, and the grey matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…However, age, sex, and education did not significantly predict odor identification scores in the linear regression models. These findings are in accordance with structural and functional changes in the olfactory system, which have been demonstrated in previous studies, and further prove that olfactory impairment is associated with processes of AD itself and cannot be explained by other factors that have been proven to influence olfaction in the general population, such as age and sex [24][25][26][27][28][29] . As olfactory and memory systems are known to significantly overlap anatomically and both are affected by cholinergic deficit, present in AD, the relationship between olfactory and cognitive impairment might be related pathogenetically.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, age, sex, and education did not significantly predict odor identification scores in the linear regression models. These findings are in accordance with structural and functional changes in the olfactory system, which have been demonstrated in previous studies, and further prove that olfactory impairment is associated with processes of AD itself and cannot be explained by other factors that have been proven to influence olfaction in the general population, such as age and sex [24][25][26][27][28][29] . As olfactory and memory systems are known to significantly overlap anatomically and both are affected by cholinergic deficit, present in AD, the relationship between olfactory and cognitive impairment might be related pathogenetically.…”
Section: Discussionsupporting
confidence: 91%
“…Structures involved in the processing of olfactory information (especially entorhinal and transentorhinal areas) are affected by AD pathology early in the course of the disease 24,25 . Functional magnetic resonance imaging (fMRI) and [18F]-fluorodeoxyglucose PET (FDG-PET) also confirmed structural and functional abnormalities of olfaction-related regions in AD patients as early as SCD [26][27][28][29] .…”
mentioning
confidence: 85%
“…The hippocampus plays a critical role in cognition ( Lisman et al, 2017 ). A previous study found that SCD exhibits a consistent pattern of hippocampal atrophy ( Chen et al, 2021 ). Some studies have observed a decreased hippocampal volume in individuals with SCD both at baseline and during a significant longitudinal decline ( Scheef et al, 2012 ; Sánchez-Benavides et al, 2018 ; van Rooden et al, 2018 ; Yue et al, 2018 ), with an annual decrease of 1.9% ( Cherbuin et al, 2015 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 93%
“…One intriguing aspect identified in the literature is that both SARS-CoV-2 infections and neurodegenerative diseases [ 30 , 31 ] (AD in particular) may lead to an impairment of the olfactory system. Anosmia, the loss of sense of smell, is one of the first and most frequent symptoms of COVID-19, and an estimated 85% to 98% of patients experience some degree of olfactory dysfunction [ 32 ].…”
Section: Introduction and Motivation Of The Workmentioning
confidence: 99%